Ten year stretch celebrating a decade of crime fiction at CrimeFest - Edwards, Martin 1955-; Muller, Adrian; Beverly, William 1965-; Brett, Simon; Child, Lee; Cleeves, Ann; Deaver, Jeffery; Edwards, Martin 1955-; Ellis, Kate 1953-; Guttridge, Peter; Hannah, Sophie 1971-; Harvey, John 1938-; et al. (No Exit Press, 2018)
The twenty brand new crime stories in this book have been specially commissioned to celebrate the tenth anniversary of CrimeFest, described by the Guardian as "one of the 50 best festivals in the world." Contributors come from around the world and include the legendary Maj Sjöwall who, together with partner Per Wahlöö, was the originator of Nordic noir. The editors are Martin Edwards and Adrian Muller. Martin Edwards is responsible for many award-winning anthologies and Adrian Muller is one of the co-founders of CrimeFest
Keywords: Criminal investigation / Fiction; Murder / Fiction; Criminal investigation; Murder; Detective and mystery fiction; Fiction; Short stories; Mystery fiction